Concentración de aceite esencial de albahaca morada encapsulado y tiempo de inmersión sobre las características organolépticas y capacidad antimicrobiana en queso - Bermello Ochoa, Stephany Judith (2020)
The purpose of this research is to determine the immersion time and the addition of encapsulated holy basil essential oil. The variables evaluated were the organoleptic characteristics and antimicrobial capacity in fresh cheese. This experimental type investigation was subjected to a completely randomized block design (DBCA) in a bifactorial arrangement A * B where combinations were established between the variable percentages of solution of essential oil of holy basil microcapsules (5 %, 10 % and 15 %), factor A and immersion time (15, 30 and 60 minutes), factor B; being the block, the panelists, having a total of 9 treatments. Encapsulation was carried out by the ionic gelation method and the acceptability of the treatments was evaluated, then the variables of microbiological capacity, humidity and organoleptic analyzes were analyzed at days 7, 14 and 21. The best efficiency of the microcapsules was the concentration of sodium alginate at 4 % and essential oil at 20 %. It was determined that the most accepted treatments for the flavor and texture parameter was T4 (10 % encapsulated holy basil essential oil solution and 15 minutes immersion). The results showed significant changes in the flavor and texture attributes, while in the color attribute the results were not significant. All treatments showed an absence of Salmonella and E. coli. It was concluded that the application of encapsulated holy basil essential oil was able to control the proliferation of microorganisms.